"Out of the Depths I Cry to You"1: Into the Dark Unknown Depths — Two-in-Oneness. Issue 2 (17th February 2020) - Eshel, Ofra
ABSTRACT: The article introduces a fundamental dimension of analytic work that is created by the analyst/therapist's "presencing" (being there) within the patient's experiential world and within the grip of the process, and the ensuing patient–analyst two-in-oneness. This dimension, with its profound ontological implications, engenders markedly new possibilities for extending the reach of psychoanalytic treatment to more and most disturbed patients and the most difficult treatment situations. It goes beyond recent analytic notions of intersubjectivity and witnessing to more radical patient-analyst deep-level interconnectedness or "withnessing" that may grow into at-one-ment or being-in-oneness with the patient's innermost emotional reality of unthinkable breakdown and catastrophic psychic trauma. Using a case example written by psychiatrist Yaron Gilat, the author illustrates the kind of knowledge, experience, and powerful transformative effects that come into being when the therapist interconnects psychically with the patient in living through extremely dark, unknown process in a difficult treatment with a severely disturbed patient.